Effectiveness of an innovative oral hygiene product in patients with obesity and type 2 diabetes mellitus in regulating appetite and food preferences - Fatima K. Dzgoeva; Elena A. Karton; Irina G. Ostrovskaya; Ekaterina A. Shestakova; Anastasiia V. Anokhina; Marina V. Shestakova (Consilium Medicum)
Background. Diabetes mellitus (DM) and obesity are diseases that lead to systemic complications that shorten life expectancy and reduce quality of life. Treatment and control of these diseases can reduce the risk of complications. However, existing lifestyle change programs and drug therapy have limited effectiveness, and therefore, the search for new methods of treating diabetes and obesity is still relevant.